The Brazilian Rise and the Elusive South American Balance - Schenoni, Luis Leandro (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2014)
Within the last fifty years, the Brazilian share of South American power has increased from one-third to one-half of the overall material capabilities in the region. Such a significant change in the regional power structure cannot have gone unnoticed by Brazil’s neighbors. The article addresses the main question related to South American unipolarity (1985–2014): Why have most countries in the region not implemented any consistent balancing or bandwagoning strategies vis-à-vis Brazil? Drawing on neoclassical realism, the article proposes that certain domestic variables – government instability, limited party-system institutionalization, and powerful presidents – have diverted the attention of political elites and foreign policy executives from the challenges generated by a rising Brazil. Crisp-set qualitative comparative analysis is used to test this hypothesis and other, alternative explanations for the regional imbalance.